MENGATASI TRAUMATIK PADA WANITA KORBAN PELECEHAN SEKSUAL MELALUI PENDEKATAN RATIONAL EMOTIVE BEHAVIOUR THERAPY - Martinaloka, Jesi; Hidayati, Richma; Kiswantoro, Arista (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
Victims of sexual harassment certainly experience stress and trauma. Because the perpetrators of sexual harassment are usually the closest relatives. Trauma is a condition where things from the past leave an impression and get trapped in the brain, causing a lot of suffering for the person who experienced the trauma. Sexual harassment is sexual activity that occurs through physical or non-physical contact with a person's genitals or sexuality. Perpetrators of sexual harassment are synonymous with whistling, flirting, uttering sexually suggestive words, showing pornographic material and showing sexual desire, poking or touching any part of the body, making sexual gestures. Rational Emotive Behavior Therapy (REBT) is a psychotherapy based on the premise that people are born with the ability to think rationally and honestly, and not to think irrationally. People tend to look after themselves, to be happy, to think and speak, to love, to relate to others and to grow and self-actualize. This research uses a case study qualitative research approach. Research was carried out in Kudus Regency in 2021/2022, with the counselee with the initials FS. Data collection techniques used are interview and observation techniques. The data analysis used is bacon system data analysis.The results of applying Rational Emotive Behavior Therapy to women victims of sexual harassment have a positive impact on reducing trauma. This is proven by the change that previously the counselee often daydreams and thinks negatively, the counselee has changed his negative thoughts with positive thoughts and prefers positive activities compared to daydreaming.